Pengembangan Obyek Wisata Telaga Menjer Kabupaten Wonosobo dan Peran Masyarakat dalam Mitigasi Bencana - Wening Rinasari; Suwarno Suwarno (UM Purwokerto Press, 2022)
The rise of ecotourism trends in various regions in Indonesia makes tourism activities an alternative for the community in increasing family income, regional income from the tourism sector also increases so that regional development increases. Many people develop interesting and unique tourism objects to attract tourists, both domestic and foreign tourists. Menjer Lake tourism object is a mainstay tourist attraction in Wonosobo Regency which has a tourist attraction, not only Menjer Lake is being developed, but the area around Menjer Lake which is in the form of hills has also developed a tourist attraction that offers views of Menjer Lake seen from the top of the hill. The question in this study is what are the disasters that may occur in the Menjer Lake tourism object and its surroundings related to the development of tourism objects? How is the role of the community around the Menjer Lake tourism object and its surroundings on the use of land for tourism development? The purpose of the study was to determine the disaster mitigation carried out by the community around the Menjer Lake tourism object and its surroundings. The object of research is the community around the Menjer Lake tourism object and its surroundings. The research method uses a qualitative approach. Observational data collection techniques and observations. Data analysis was carried out through four stages, namely data collection, data condensation, data presentation and drawing conclusions. The results showed that the disasters that often occur in Menjer Lake and its surroundings are landslides and floods. The role of the community in disaster mitigation tends to increase due to public awareness in disaster response.